Discovery of new MurA inhibitors using induced-fit simulation and docking. Issue 4 (15th February 2017) - Rožman, Kaja; Lešnik, Samo; Brus, Boris; Hrast, Martina; Sova, Matej; Patin, Delphine; Barreteau, Hélène; Konc, Janez; Janežič, Dušanka; Gobec, Stanislav
Graphical abstract: Abstract: We report on the successful application of ProBiS-CHARMMing web server in the discovery of new inhibitors of MurA, an enzyme that catalyzes the first committed cytoplasmic step of bacterial peptidoglycan synthesis. The available crystal structures of Escherichia coli MurA in the Protein Data Bank have binding sites whose small volume does not permit the docking of drug-like molecules. To prepare the binding site for docking, the ProBiS-CHARMMing web server was used to simulate the induced-fit effect upon ligand binding to MurA, resulting in a larger, more holo-like binding site. The docking of a filtered ZINC compound library to this enlarged binding site was then performed and resulted in three compounds with promising inhibitory potencies against MurA. Compound1 displayed significant inhibitory potency with IC50 value of 1 μM. All three compounds have novel chemical structures, which could be used for further optimization of small-molecule MurA inhibitors.